China-led BRI and its Impact on India with Specific Reference to CPEC - Awasthi, Soumya (Journal of International Affairs, 2018)
Given China’s proactive international diplomacy today, it continues to make its presence felt in the region. The ambitious project of Belt and Road Initiatives (BRI) stands among the widest reaching of all other initiatives. It not only represents a renewed, stronger and better co-ordinated push to expand China’s influence overseas but is also coupled with a domestic investment drive, in which nearly every Chinese province has a stake. BRI is a set of two outward-facing models introduced by the Chinese President Xi Jinping in 2013 to promote economic engagement and investment along two main routes: the New Silk Road and the Maritime Silk Route. The proposed countries under the BRI framework are close to 68 countries, with up to 40 per cent of the Global GDP (Griffiths, 2017). This article looks at four major issues. First, what comprises BRI and what it has for the partners in the project? Second, what does it mean for India with specific reference to China Pakistan Economic Corridor (CEPC)? Third, major concerns in BRI and CEPC. Finally, the article also discusses the available options for India reluctant to join BRI.